Synthesis of 2-substituted quinolines from alcohols. Issue 24 (10th June 2015) - Xu, Xuefeng; Zhang, Xu; Liu, Wenming; Zhao, Qiang; Wang, Zhiqiang; Yu, Lintao; Shi, Fu
Graphical abstract: A facile and economic method for the construction of 2-substituted quinolines by AgOTf-catalyzed 2-aminobenzyl alcohol and alkyne/ketone or 2-aminophenethyl alcohol and aldehyde has been developed. The electronic properties of the substituents on the alkyne, ketone, and aldehyde were investigated. It was found that molecules with both electron-donating and -withdrawing substituents were perfectly suitable substrates for this transformation, and the expected products were obtained in moderate to excellent yields. Moreover, the use of inexpensive starting materials and environmentally benign oxidants makes this atom efficient method particularly attractive. Abstract: A facile and economic method for the construction of 2-substituted quinolines by AgOTf-catalyzed 2-aminobenzyl alcohol and alkyne/ketone or 2-aminophenethyl alcohol and aldehyde has been developed. The electronic properties of the substituents on the alkyne, ketone, and aldehyde were investigated. It was found that molecules with both electron-donating and -withdrawing substituents were perfectly suitable substrates for this transformation, and the expected products were obtained in moderate to excellent yields. Moreover, the use of inexpensive starting materials and environmentally benign oxidants makes this atom efficient method particularly attractive.